Challenges and resiliency in Aboriginal adults with Fetal Alcohol Spectrum Disorder - Samaroden, Melanie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2018)
Aboriginal adults with Fetal Alcohol Spectrum Disorder (FASD) face multiple barriers to services that did not exist in their childhood, yet they still cope with the same FASD-related cognitive issues that they experienced in childhood. Considerable effort is directed to research on children with FASD, but little research on adults with FASD. Furthermore, research on the population of Canada that is generalized to Aboriginal people is neither effective nor ethical. This literature review focuses on Aboriginal adults with FASD, specifically looking at criminal recidivism rates, the stigma attached to an FASD diagnosis, lack of support services, and the ongoing effects of intergenerational trauma. Future qualitative research is suggested to focus on adulthood and aging with FASD, and on helpful interventions.